2013
DOI: 10.1016/j.jjcc.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional co-expression network analysis of familial hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is an inherited disorder of blood lipid metabolism characterized by high serum low-density lipoprotein cholesterol levels and premature coronary artery disease. In this study, we used a system biology approach to identify co-expressed gene pairs that were potentially involved in the progression of FH and constructed a conserved co-expression network using these genes. A total of 4232 co-expressed relationships were identified and we verified the significance by random permuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…2). We report the most current studies applying integrated network‐oriented analysis to identify putative risk biomarkers and drug targets (Table 1) (Adiels et al, 2018; Chen et al, 2014; Miao et al, 2019; Wang and Loscalzo, 2018; Yao et al, 2015; Ye et al, 2013).…”
Section: Network‐oriented Analysis For Primary Prevention Of Dyslipidemias and Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…2). We report the most current studies applying integrated network‐oriented analysis to identify putative risk biomarkers and drug targets (Table 1) (Adiels et al, 2018; Chen et al, 2014; Miao et al, 2019; Wang and Loscalzo, 2018; Yao et al, 2015; Ye et al, 2013).…”
Section: Network‐oriented Analysis For Primary Prevention Of Dyslipidemias and Atherosclerosismentioning
confidence: 99%
“…By using available microarray datasets performed on T cells and monocytes isolated from FH patients, a co‐expression network of differentially expressed (DE) transcripts was built. The analysis revealed a set of perturbed gene pairs in cholesterol lipoprotein metabolism (Ye et al, 2013). Remarkably, through a GO analysis, chronic myeloid leukemia, neurotrophin signaling pathway, and SNARE protein interactions in vesicular transport have been suggested, as key deregulated signaling pathways in FH (Ye et al, 2013).…”
Section: Network‐oriented Analysis For Primary Prevention Of Dyslipidemias and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Gallium-68, labelled DOTATATE, targets the somatostatin receptor subtype 2 (SSTR2) found on the surface of macrophages. Pre-clinical studies have confirmed 68 Ga-DOTATATE's superiority over FDG in terms of macrophage specificity in atherosclerotic inflammation and in discriminating between unstable and stable coronary plaques 54) . 18 F-fluorocholine ( 18 F-FCH), a PET tracer with potential antiinflammatory affinity, shows a strong association between large vessel uptake and atherosclerotic changes in the arterial walls, with an apparent inverse relationship with calcification 54) .…”
Section: Cardiovascular Consortia For Precision Medicine Implementationmentioning
confidence: 90%
“…2), 18 of which were associated with the cardiovascular system, confirmed the key functional role of seed connectors functional pathways of leukocyte subsets from FH patients and healthy individuals. A total of 4,232 coexpressed relationships were identified in patients showing dysregulation in lipoprotein and cholesterol metabolism as well as neurotrophin signaling (SNARE proteins), MAPK pathways, and endocytosis processes, suggesting an altered transport of low-density lipoprotein receptor (LDLR) across membrane 68) .…”
Section: Fig 2 Nodes Edges and Molecular Network Analysismentioning
confidence: 99%